Caregiver Perception of Weight Status in 5-Year-Old Children From a Community of High Socioeconomic Deprivation in New Zealand - Éadaoin M. Butler; Éadaoin M. Butler; José G. B. Derraik; José G. B. Derraik; José G. B. Derraik; José G. B. Derraik; Alison Burge; Wayne S. Cutfield; Wayne S. Cutfield; Alison Leversha; Alison Leversha (Frontiers Media S.A., 2022)
BackgroundEarly childhood obesity is highly prevalent in Aotearoa New Zealand (NZ). Little is known about caregiver perception of children's weight status among those living in areas of high socioeconomic deprivation, particularly Māori and Pacific children.AimsTo explore caregiver perception of weight status among children starting school in areas of high socioeconomic deprivation and examine potential associations between the child's body mass index (BMI) z-score and their caregiver's perception of their child's body size or health.MethodsParticipants were 5-year-old children living in a community of high socioeconomic deprivation and their caregivers. Children had their weight and height measured. BMI z-scores were calculated according to World Health Organization standards. Caregivers were asked to assess their child's BMI and health status, and choose a silhouette that best represented their child's body size.ResultsOne hundred and six children (>75% Māori or Pacific) were included. Over half (58%) had overweight or obesity, with only 16% correctly perceived by their caregiver as overweight. These children tended to have higher BMI z-scores than those not correctly perceived as overweight. Caregivers chose larger silhouettes to represent children's body sizes as children's BMI z-scores increased. There was no discernible association between children's BMI z-scores and caregiver perception of children's health.ConclusionsCaregivers appeared to judge their child's body size in comparison to other children. The normalization of childhood obesity and infrequent caregiver recognition of this condition in children in communities with a high prevalence may impact the uptake and efficacy of intervention initiatives.